SECURE AND EFFICIENT METHOD FOR DYNAMIC ECONOMIC LOAD DISPATCH IN LARGE POWER SYSTEMS - Ab Ghani, Mohd Ruddin (2000)
This paper presents an efficient and secure method of solving dynamic economic load dispatch (DELD) scheduling problems for large-scale power system operation systems. The main objective is to reduce the total operation costs into the lowest possible level while considering system operation constraints. The method uses LaGrangian Relaxation Method, Linear Programming and other techniques. The algorithm used appears to be efficient and secure to meet the required scheduling objectives of the system. After real system individual generators are economically loaded and periodically dispatched, optimized total generation cost and fast computation times have been achieved. DELD with different period intervals has been taken into consideration. Promising results have been achieved using different real data systems.